2018
DOI: 10.1177/0960327118812166
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D attenuates gentamicin-induced acute renal damage via prevention of oxidative stress and DNA damage

Abstract: Background: Despite being one of the most nephrotoxic drugs, gentamicin (GM) remains a mainstay as a first-choice agent in a vast variety of clinical situations owing to its superlative efficiency as a broad-spectrum antibiotic in treating several life-threatening bacterial infections. This urgently calls for the need for in-depth analysis of the mechanisms governing GM-induced nephrotoxicity and entails the necessity of presenting novel protective agents capable of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A number of studies confirmed the crucial role of vit D 3 as a potent antioxidant. 59 61 Additionally, many studies have displayed the role of vit D 3 in the regulation of inducible form of NOS. 62,63 Garcion et al 62 mentioned that vit D 3 exerts its protecting effects through preventing free radical formation by the reactive species of nitric oxide and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies confirmed the crucial role of vit D 3 as a potent antioxidant. 59 61 Additionally, many studies have displayed the role of vit D 3 in the regulation of inducible form of NOS. 62,63 Garcion et al 62 mentioned that vit D 3 exerts its protecting effects through preventing free radical formation by the reactive species of nitric oxide and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression of β-actin was considered as the internal control, and all the assessment and analysis of all data was processes using the comparative cycle threshold (CT) method. The primers used for Nrf2 , NF-κB and β-actin were (Nrf2; Forward primer: 5′-GCT GCA GAA GCA AGA GAA CC-3′ and Reverse primer: 5′-GGCAGTGAAGACTGAACTTTCA-3′, GenBank accession number NM031789.2 58 , NF-κB; Forward primer: 5′-CATTGAGGTGTATTTCACGG-3′, Reverse primer :5′-GGCAAGTGGCCATTGTGTTC-3′, GenBank accession number NM199267.2) 59 , β-actin; Forward primer: 5′-GACGGCCAGGTCATCACTAT-3′, Reverse primer: 5′-CTTCTGCATCCTGTCAGCAA-3′, GenBank accession number XM011332812.3 ) 58 .…”
Section: Methodsmentioning
confidence: 99%
“…14 Vitamin D 3 has anti-oxidative properties, reduces inflammatory response, and improves immunity. 15,16 Vitamin D 3 is also effective in inflammatory bowel disease, 17 pulmonary fibrosis, 18 and renal fibrosis. 19 However, little is known about the role of vitamin D 3 in CP-induced intestinal injury; in particular, the relationship between vitamin D 3 and intestinal oxidative stress and ferroptosis is not known.…”
Section: Introductionmentioning
confidence: 99%